Development of a Core Set of Outcomes for Randomized Controlled Trials with Multiple Outcomes – Example of Pulp Treatments of Primary Teeth for Extensive Decay in Children - Smaïl-Faugeron, Violaine (Public Library of Science, 2013)
OBJECTIVES: Evidence-based comparisons of interventions can be challenging because of the diversity of outcomes in randomized controlled trials (RCTs). We aimed to describe outcomes in RCTs assessing pulp treatments for primary teeth and to develop a core set of component outcomes to be part of composite outcome defining the failure of a pulp treatment. METHODS: We systematically reviewed articles of RCTs comparing pulp treatments for primary molars published up to February 2012. We abstracted all outcomes assessed in each trial, then used a small-group consensus process to group similar outcomes, which were reduced to a composite outcome of failure of a pulp treatment by a 3-round Delphi process involving expert authors and dentists. RESULTS: We included 47 reports of RCTs in the review, for 83 reported outcomes (median 11 outcomes per RCT). These outcomes were grouped into 24 overarching outcome categories. We contacted 210 experts for the Delphi process and 25% to 30% participated. The process identified the following 5 component outcomes as part of a composite outcome of failure of a pulp treatment: soft-tissue pathology, pain, pathologic mobility, pathologic radiolucency and pathologic root resorption. CONCLUSIONS: RCTs of pulp treatments for primary teeth investigate diverse outcomes. Our consensus process, involving clinicians but no patient, allowed for compiling a core set of component outcomes to define the composite outcome failure of a pulp treatment for primary teeth.